Mathematical modelling of multiwave volume free electron laser: Basic principles and numerical experiments - Batrakov, K.; Sytova, S. (Mathematical Modelling and Analysis, 2006)
This contribution is devoted to investigation of multiwave Volume Free Electron Laser (VFEL) by methods of mathematical modelling. Special emphasis is placed on consideration of three‐wave VFEL. Mathematical modelling carried out confirmed some preliminary physical estimates. Computer code VOLC for simulation of different schemes of two‐ and three‐wave VFEL is described. First Published Online: 14 Oct 2010